Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1038/ejcn.2017.63
|View full text |Cite
|
Sign up to set email alerts
|

Does diet intervention in line with nutrition recommendations affect dietary carbon footprint? Results from a weight loss trial among lactating women

Abstract: A diet intervention in line with NNR 2004 produced clinically relevant weight loss, but did not reduce dietary CF among lactating women with overweight and obesity. Dietary interventions especially designed to decrease dietary CF and their coherence with dietary recommendations need further exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Because the current study observed the environmental impact of dietary changes in a real-life setting, it may We found that the increased impacts on GHGE and LU from the increased intake of fruit, vegetables, fish, pulses/ legumes, and whole grains were collectively offset by the reduced impacts on GHGE and LU from the decreased intake of sweets/extras. Our results are in line with the weight loss trial which found that a reduction in intake of sweets, snacks, and soft drinks and an increase in intake of fruit and vegetables led to no change in overall carbon footprint of the diet [20]. However, we found that observed dietary change led to an increase in FEU of the overall diet, which may be attributable to the relative increase in fish, as fisheries are generally energy-intensive operations [62,63].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Because the current study observed the environmental impact of dietary changes in a real-life setting, it may We found that the increased impacts on GHGE and LU from the increased intake of fruit, vegetables, fish, pulses/ legumes, and whole grains were collectively offset by the reduced impacts on GHGE and LU from the decreased intake of sweets/extras. Our results are in line with the weight loss trial which found that a reduction in intake of sweets, snacks, and soft drinks and an increase in intake of fruit and vegetables led to no change in overall carbon footprint of the diet [20]. However, we found that observed dietary change led to an increase in FEU of the overall diet, which may be attributable to the relative increase in fish, as fisheries are generally energy-intensive operations [62,63].…”
Section: Discussionsupporting
confidence: 90%
“…While these studies have predominately examined the environmental impact of hypothetical change from current to proposed diets, there is limited research on the environmental impact of dietary change in a real-life setting. Only one previous study has examined changes in GHGE related to changes in food choice in overweight women who received a diet plan based on the Nordic Nutrition Recommendations 2004 and found no effect on diet-associated GHGE, although the women increased their fruit and vegetable intake and decreased total caloric intake compared to those who did not receive the diet plan [20]. Thus, the environmental impact of dietary change in line with dietary guidelines in a real-life setting needs further investigation.…”
Section: Introductionmentioning
confidence: 98%
“…Food system (cultivation, processing, packaging, distribution, consumption, and waste), which is mainly associated with Greenhouse Gases Emission (GHGEs), water requirements, and land use, may affect the environment negatively (Vermeulen et al, 2012;Gustafson et al, 2016;Huseinovic et al, 2017;González-García et al, 2018). The food system is responsible for more than a quarter of all GHGEs (Vermeulen et al, 2012;Springmann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, less meat consumption and high plantbased food consumption contributes positively to the environment by decreasing GHGEs (Tilman and Clark, 2014). However, studies investigating the sustainability of diets, showing their effects on environment, and nutrition differ according to the type of food (Huseinovic et al, 2017). Drewnowski et al (2015) reported that although many foods such as sugar have low climate impact, they also have low nutritional value.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies indicating good opportunities for sustainable diets promoting better health and benefiting the environment ( 16–20 ). However, dietary patterns with a lower climate impact will not necessarily improve nutrient density or health outcomes ( 21 ), and dietary interventions based on nutrition recommendations have moreover shown that changes toward healthier dietary patterns in practice may not lead to decreased climate impact ( 22 ). In short, choosing diets beneficial for both health and climate is not obvious for consumers, and it is also not obvious how policy and dietary guidelines should be designed to benefit both perspectives.…”
Section: Introductionmentioning
confidence: 99%